Peningkatan Keterampilan Berpikir Kritis Melalui Model Discovery Learning - Sa'diyah, Awalus; Dwikurnaningsih, Yari (Universitas Muhammadiyah Magelang, 2019)
This research aims to improve critical thinking skills on thematic learning of fourth-grade elementary school through discovery learning model. The design of the study was based on classroom action research by Kemmis & McTaggart with two cycles. This research procedure was done by implementing discovery learning model which was planned, action, observation, and reflection. The quantitative and qualitative data were compared to the data analysis technique. The sample of this research was eighteens fourth-grade public elementary school in Kutowinangun 11. The results showed that implementation discovery learning model in thematic learning could increase critical thinking skills’ student of the fourth-grade public elementary school in Kutowinangun 11with average of an increasing percentage of critical thinking skills was 16.04%, with the average score in cycle 1 was 68 and cycle 2 was 81. Increasing critical thinking skills occurs through discovery learning steps includes stimulation, problem statements, data collection, data processing, verification, and generalization.